Are bone morphogenetic protein-7 (BMP-7) serum levels correlated with development of hepatic fibrosis? - Nazlim Aktug Demir; Servet Kolgelier; Ahmet Cagkan Inkaya; Sua Sumer; Lutfi Saltuk Demir; Fatma Seher Pehlivan; Mahmure Arslan; Abdullah Arpaci (Journal of Infection in Developing Countries)
Introduction: Bone morphogenetic protein-7 (BMP-7) is a key protein in organogenesis and liver development. The protein has been studied in the context of liver fibrosis and regeneration. The aim of the present study was to explore any possible association between fibrosis levels (as revealed by liver biopsy) and serum BMP-7 levels. Methodology: A total of 189 patients with chronic hepatitis B and 51 healthy controls were enrolled in the study. Results: The study group contained 120 (63.5%) males and 69 (36.5%) females, and the control group contained 25 males (49.0%) and 26 females (51%). In general, serum BMP-7 values of patients were higher than those of controls (p = 0.001). Serum BMP-7 values of patients with liver fibrosis of stages 1, 2, 3, or 4 were higher than control values (all p values = 0.01), but the serum BMP-7 levels of patients with stage 5 fibrosis were similar to that of controls. Associations between fibrosis stage and the serum levels of BMP-7, ALT, HBVDNA, platelets, and albumin were all statistically significant (p = 0.001). The AUROC for the BMP-7 level in advanced stage fibrosis was found to be 0.23. The data were analyzed using the binary logistic regression analysis (backward stepwise method) and BMP-7, HBVDNA, and platelet levels were found to be risk factors associated with fibrosis (p values 0.031, 0.040, and 0.001, respectively). Conclusions: BMP-7 may play anti-inflammatory and anti-fibrogenic roles in the pathogenesis of chronic hepatitis B infection.